Orwell : 2+2=5 [videorecording (DVD)] - Orwell, George, 1903-1950 (Neon, 2026)
George Orwell was one of the most visionary authors of the 20th Century, whose novels, 1984 and Animal Farm, foretold a chilling, authoritarian future. Acclaimed director Raoul Peck (I Am Not Your Negro) interweaves clips, readings from Orwell's diary, cinematic references, and modern-day footage to craft not only a portrait of the writer, but a fresh take on how prophetic his work has become.